{Genome-Wide Association Study of Apparent Treatment-Resistant Hypertension in the CHARGE Consortium: The CHARGE Pharmacogenetics Working Group - Irvin, M. R.; Sitlani, C. M.; Floyd, J. S.; Psaty, B. M.; Bis, J. C.; Wiggins, K. L.; Whitsel, E. A.; Sturmer, T.; Stewart, J.; Raffield, L.; Sun, F.; Liu, C. T.; et al. (Am J Hypertens, 2019)
{Only a handful of genetic discovery efforts in apparent treatment-resistant hypertension (aTRH) have been described.\ We conducted a case-control genome-wide association study of aTRH among persons treated for hypertension, using data from 10 cohorts of European ancestry (EA) and 5 cohorts of African ancestry (AA). Cases were treated with 3 different antihypertensive medication classes and had blood pressure (BP) above goal (systolic BP ≥ 140 mm Hg and/or diastolic BP ≥ 90 mm Hg) or 4 or more medication classes regardless of BP control (nEA = 931

{Discovery of rare variants associated with blood pressure regulation through meta-analysis of 1.3 million individuals - Surendran, P.; Feofanova, E. V.; Lahrouchi, N.; Ntalla, I.; Karthikeyan, S.; Cook, J.; Chen, L.; Mifsud, B.; Yao, C.; Kraja, A. T.; Cartwright, J. H.; Hellwege, J. N.; et al. (Nat Genet, 2020)
Genetic studies of blood pressure (BP) to date have mainly analyzed common variants (minor allele frequency > 0.05). In a meta-analysis of up to 1.3 million participants, we discovered 106 new BP-associated genomic regions and 87 rare (minor allele frequency ≤ 0.01) variant BP associations (P < 5 × 10-8), of which 32 were in new BP-associated loci and 55 were independent BP-associated single-nucleotide variants within known BP-associated regions. Average effects of rare variants (44% coding) were 8 times larger than common variant effects and indicate potential candidate causal genes at new and known loci (for example, GATA5 and PLCB3). BP-associated variants (including rare and common) were enriched in regions of active chromatin in fetal tissues, potentially linking fetal development with BP regulation in later life. Multivariable Mendelian randomization suggested possible inverse effects of elevated systolic and diastolic BP on large artery stroke. Our study demonstrates the utility of rare-variant analyses for identifying candidate genes and the results highlight potential therapeutic targets.